Digital participation for marine waste management in Batam, Indonesia through theory of planned behavior and adaptive capacity - Nova Ulhasanah; I Wayan Koko Suryawan (Journal of Sustainable Infrastructure, 2026)
This study examines the determinants of community digital participation in marine waste management in Batam, Indonesia, focusing on the roles of adaptive capacity, attitudes, subjective norms, perceived behavioral control, and intention. A structured survey of 450 respondents was conducted, and the data was analyzed using Structural Equation Modeling (SEM). The descriptive analysis shows that respondents strongly recognize the importance of social media in protecting Batam’s coastal environment and receiving encouragement from family and peers, yet actual behavioral participation remains relatively low. Measurement results confirm that all construction demonstrates high reliability and validity, with the model explaining 62.2% of the variance in willingness to participate. Structural relationship testing reveals that adaptive capacity exerts the strongest direct effect on both intention (β = 0.79, p < 0.001) and willingness to participate (β = 0.613, p < 0.001), while intentions significantly predict willingness to participate (β = 0.775, p < 0.001). In contrast, attitudes, subjective norms, and perceived behavioral control have indirect or nonsignificant direct effects. These findings suggest that digital participation in environmental initiatives depends less on awareness alone and more on adaptive skills and motivational commitment. The study highlights the importance of digital literacy, capacity building, and intention-driven interventions for strengthening marine waste management in emerging coastal cities.